2017
DOI: 10.25036/jphr.2017.1.2.voight
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hip Abduction Elastic-Resisted Neuromuscular Feedback on Frontal Plane Knee Kinematics in Female Volleyball Athletes

Abstract: Background: In female athletes, the knee is one of the most commonly injured areas of the body. Uncontrolled frontal plane knee motion or "valgus collapse" has been identified as a risk factor for knee injury. This movement pattern has been observed in cases of anterior cruciate ligament (ACL) tears in athletes and it has also been linked to the development of patellofemoral pain syndrome. While often seen during a body-weight squatting maneuver, the valgus collapse is magnified when the athlete either lands f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“… 98 Many athletes spent much time using serious apps for self-management, which include image analysis, scheduling, diet, and sleep. 99 100 101 102 Smartphone usage time had no significant correlation with academic achievement; previous findings confirm that keeping smartphones out of reach led to academic success contradicts this finding. 103 104 Smartphone usage patterns had a relatively higher impact on academic performance compared with smartphone usage time.…”
Section: Discussionmentioning
confidence: 85%
“… 98 Many athletes spent much time using serious apps for self-management, which include image analysis, scheduling, diet, and sleep. 99 100 101 102 Smartphone usage time had no significant correlation with academic achievement; previous findings confirm that keeping smartphones out of reach led to academic success contradicts this finding. 103 104 Smartphone usage patterns had a relatively higher impact on academic performance compared with smartphone usage time.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast to the negative effects of smartphone apps on sports performance, several apps have been used to improve it. In particular, smartphone apps have been applied to control sleep time schedules and sport performance analyses ( Roos, 2014 ; Voight et al, 2017 ; Balsalobre-Fernández et al, 2018 ; Budiono et al, 2018 , 2019 ; Harris et al, 2018 ). Harris et al (2018) reported that smartphone learning apps could improve sports performance by encouraging identity, goal awareness, positive reinforcement, and the need for convenience with limited time.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of surveys of golfers and golf coaches, a video analysis app for golfers helped to improve overall golf performance, including stance, balance, and swing ( Roos, 2014 ). A neuromuscular training program smartphone app improved jump-correcting lower-limb alignment during drop-jump, take-off, and landing tasks in volleyball players ( Voight et al, 2017 ). Performance analysis apps can be highly specialized for the different components of athletes’ performance.…”
Section: Discussionmentioning
confidence: 99%